Success and Failure of National Dialogues: Selected Countries' Case Studies: General Lessons for Ethiopia - Surafel Getahun Ashine (European Scientific Journal, ESJ, 2026)
This paper aims to analyze the successes and failures of national dialogue by drawing lessons for Ethiopia from the experience of other nations that have undertaken national dialogue in challenging political environments. Using a qualitative research methodology, this study analyzed the national dialogue conducted from 1990 to 2016. Countries selected as part of the case study were South Africa, Afghanistan, Sudan, Yemen, Iraq, and Tunisia. Document analysis was utilized to glean information on the characteristics shared by all national dialogues, as well as the political and procedural elements and circumstances that have either facilitated or impeded the negotiated outcomes of national dialogues. The study found that while the majority of the National Dialogues under study came to agreements, in half of the cases, the agreements were not executed or were only partially implemented. This paper made the case that for Ethiopia's national dialogue to be successful and to end the persistent conflict and holistically address the underlying causes of conflict, the national dialogues should be considered beyond the typical circle of elitist decision-makers. According to the article as a whole, national dialogues will be more likely to succeed if they include the following principles: political will, inclusiveness, openness, and public engagement, a broad agenda, an implementation plan, suitable and understandable rules of procedure, and a trustworthy convener.